2019
DOI: 10.1186/s12893-018-0457-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the ultrasonic, bipolar and integrated energy devices in the adrenal gland surgery: literature review and our experience

Abstract: Background: The gold standard approach for surgical treatment of benign and malignant adrenal lesion is considered the laparoscopic one, due to a lot of advantages compared to open approach. The rapid propagation of this surgical technique is due to the diffusion of haemostatic devices in laparoscopic adrenal surgery. The principal aim of this study is to analyze the outcome of LA using each energy modality, evaluating the eventual superiority of an instrument over the others. Methods: A retrospective study, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
(36 reference statements)
0
21
0
Order By: Relevance
“…Several studies have concluded that the TB can be as safe as other energy-based devices when used in laparoscopic surgery [20][21][22], thyroid surgery [11] and neck dissections [10]. This study has indicated that the TB is at least as safe as the SED during TL and ND, as the statistically insignificant difference was found in favor of the TB group.…”
Section: Discussionmentioning
confidence: 69%
“…Several studies have concluded that the TB can be as safe as other energy-based devices when used in laparoscopic surgery [20][21][22], thyroid surgery [11] and neck dissections [10]. This study has indicated that the TB is at least as safe as the SED during TL and ND, as the statistically insignificant difference was found in favor of the TB group.…”
Section: Discussionmentioning
confidence: 69%
“…For one case of Cushing's syndrome, the Harmonic Scalpel and Thunderbeat devices caused hypertensive crisis. 9 There are also reports of hypertensive crisis caused by energy devices used for adrenal separation or hemostasis. [15][16][17] Adrenal ablation was carried out in four ways using a VIO300D generator.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the same output and duration of cauterization, the intensity and extent of degeneration in the adrenal gland differed pathologically depending on the type and application of the device. Although not used in this experiment, there are reports of hypertensive crisis using Thunderbeat 9 and a bipolar searing system. 17 It is not the type of device that is important in preventing hypertensive crisis, but rather, the method used based on the characteristics of the device to avoid degeneration in the medulla.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, ultrasonic, ABP and hybrid devices have been characterized as advanced energy devices in cross-specialty literature, given similarities in their various purposes, including hemostasis, sealing, transection and dissection of blood vessels, as well as technological advancements [15][16][17] . For the purpose of this work, we define advanced energy devices as electrosurgical devices that leverage recent advancements on conventional monopolar and bipolar electrosurgical instruments, such as increased compression, integrated cutting blade in ABPs, and algorithmic energy control, to achieve coagulation and transection involved in surgical procedures.…”
Section: Introductionmentioning
confidence: 99%